In vitro exposure to thiacloprid-based insecticide formulation promotes oxidative stress, apoptosis and genetic instability in bovine lymphocytes. (December 2019) - Schwarzbacherová, Viera; Wnuk, Maciej; Deregowska, Anna; Holečková, Beáta; Lewinska, Anna
Abstract: A proprietary thiacloprid-based neonicotinoid insecticide formulation is widely used in agriculture to protect vegetables and fruit against various pests. However, its effect on animal cells has not been fully elucidated. In this study, bovine peripheral lymphocytes were incubated with different concentrations of this formulation (10; 30; 60; 120 and 240 μg.mL −1 ) for 4 h to address the potential cytotoxic and genotoxic effects of the insecticide. Insecticide formulation treatment resulted in decreased cell viability and proliferation, p53-mediated cell cycle arrest at the G0 /G1 phase, and apoptosis induction accompanied by elevated levels of mitochondrial superoxide and protein carbonylation. Oxidant-based DNA damage and DNA damage response (DDR) were also observed, namely the formation of micronuclei, DNA double-strand breaks and slightly elevated recruitment of p53 binding protein (53BP1) foci. Our results contribute to the elucidation of insecticide effects on animal lymphocyte cultures after short-term exposure. Due to increased application of neonicotinoids worldwide, resulting in both higher yields and adverse effects on non-target animals and humans, further in vivo and in vitro experiments should be performed to confirm their cytotoxic and genotoxic activities during short-term exposure. Highlights: Calypso® cytotoxicity and genotoxicity was examined in cultured bovine lymphocytes. The insecticide caused decrease in cell proliferation and viability. P53 mediated cell cycle arrest at the G0 /G1 phase was found. Apoptosis was detected as a consequence of oxidative damage. Genetic instability was mediated by increased levels of oxidative damage.